A Personalized Web Cosmetic Recommendation System Based on Skin Type - Junaidi, Nor Farah Azreen; Mohd Safar, Noor Zuraidin; Abdullah, Noryusliza; Kamaludin, Hazalila (Applied Information Technology And Computer Science, 2021)
Cosmetics Recommendation System is a web-based system which helps the user to decide to choose their skincare range based on their skin type by suggesting some product recommendation that matches their skin type. User will have a survey session which to know their skin type before choosing their skincare products. Many user experience difficulties to choose the product that match their skin due to varieties of choices available online. Furthermore, there are some factors that affect the decision of users such as the product packaging, price, product rating and product review. This system will help the user to analyze their skin type, assist on suggesting products that match the user’s skin condition and also provide some skin tips to enhance their skincare knowledge and care. It can improve the efficiency and speed-up decision-making process for the user to choose their skincare product. The prototyping model is being used as the guideline and standard together with the process of system development. Fusion Charts used to visualize the decision result from data entered by the user based on the answered survey. Decision tree technique has been used to analyze the collected information. At the end of the project, testing was conducted to ensure this system acquires the needs and its functionality. It shows that the system has helped the user to make better choices for their skincare range based on their skin type.